Faktor-Faktor yang Mempengaruhi Konversi Lahan Pertanian di Subak Sebuah, Kelurahan Kerobokan, Kecamatan Kuta Utara, Kabupaten Badung, Bali - NI LUH RISKA WIRYANTINI; I WAYAN WIDYANTARA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Factors Affecting Agricultural Land Conversion in the Irrigation Organizationof Subak Sebuah, Kerobokan Urban Village, Sub-District of Kuta Utara,Badung Regency, Bali The research aimed to investigate the factors that affect the conversion of agriculturalland and the dominant factors that affect the conversion of agricultural land in thetraditional irrigation organization of Subak Sebuah, located at Kerobokan Urban Village,Sub-District of Kuta Utara, Badung Regency, Bali. The location was chosenpurposively in Subak Sebuah, Kerobokan Urban Village, Sub-District of Kuta Utara,Badung Regency, Bali. The number of respondents was 70 people by using quotasampling method. This research used factor analysis. The findings showed that factorsaffecting the conversion of agricultural land in the Subak Sebuah are economic factors(land selling price, land leasing price, farm income, household expenditure), socialfactors (following neighbors, age, and the number of family members working outsidethe agricultural sector) and land conditions factors (availability of irrigation water,access to irrigation water, land area before conversion, and location of land). Thedominant factors affecting the conversion of agricultural land in Subak Sebuah,Kerobokan Urban Village, Sub-District of Kuta Utara, Badung Regency, Bali are theeconomic factors.